AKTIVITAS SPONS LAUT Lamellodysidea herbacea DARI PERAIRAN MALALAYANG, MANADO - Sumilat, Deiske Adeliene (JURNAL LPPM BIDANG SAINS DAN TEKNOLOGI, 2017)
Marine sponge Lamellodysidea herbacea was collected from Malalayang Water North Sulawesi. Ethanol extracted was evaporated with vaccum rotary evaporator at 40 Â°C. Purification with HPLC and yielded 3 fractions. Citotoxicity test with MTT assay, fraction 2 showed cytotoxicity against HCT-15 and Jurkat cells at 10 Î¼g /mL.